PENTINGNYA PERAN SUSCATIN (KURSUS CALON PENGANTIN) DALAM MEMBENDUNG LAJU PERCERAIAN - Ulin Na'mah (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2016)
Marriage preparation course (Kursus Calon Pengantin – Suscatin) is a short course for engaged couples about domestic life. Legal basis for this course is Regulation from General Director of Islamic Community Guidance No DJ.II/491 Year 2009 renewed by No DJ.II/542 Year 2013. Therefore, the course is basically an effort made by the government – BP4 – to provide the couple with skill and psychological provision to overcome marriage problems. Thus, theidea of loving, affection and compassion in marriage may be achieved and at the same time also to realize a harmonious society and to avoid family conflict and divorce. Theoretically, materials of the marriage preparation course by Office of Religious Affairs (KUA) are comprehensive, covering: rules and procedures of marriage; religious knowledge; marriage and family laws and regulations; rights and obligations of husband and wife; female reproduction health; familymanagement; and also psychology of marriage and family. Unfortunately, the practice of the course has become a mere formality.